Association of vitamin D deficiency with post-stroke depression: a retrospective cohort study from the TriNetX US collaborative networks - Ho, Chun-Ning; Sun, Cheuk-Kwan; Wu, Jheng-Yan; Chen, Jen-Yin; Chang, Ying-Jen; Chen, I-Wen; Hung, Kuo-Chuan (Frontiers in Nutrition, 2023)
Background: Post-stroke depression (PSD) affects up to one-third of patients who survive stroke. This matched cohort study aimed to investigate the relationship between vitamin D deficiency (VDD) and PSD using a global health research network. Methods: Adult patients with first-ever stroke were eligible for inclusion if their circulating vitamin D levels were available within three months before the onset of stroke. Patients were subdivided into those with VDD [ VDD group, 25(OH) D<20 ng/mL] and those with normal vitamin D levels (control group, 25(OH) D: 30-80 ng/mL). By using propensity score matching (PSM), potential confounding factors were adjusted. The primary outcomes were the association of VDD with the risk of PSD at the 3-month and 12-month follow-ups, while the secondary outcomes were the relationships between VDD and the risk of pneumonia as well as emergency department visits at the 12-month follow-up. Results: After PSM, 758 individuals were included in each group, with no significant differences in baseline characteristics. Musculoskeletal diseases, metabolic disorders, and hypertension were the three leading comorbidities in both the groups. The incidence of PSD was not significantly different between the two groups at the 3-month (5.8% vs. 4.7%, p=0.358) and 12-month (11.6% vs. 10.2%, p=0.364) follow-up. VDD was not associated with an increased risk of PSD at the 3-month (hazard ratio [HR] = 1.258, p=0.358) or 12-month follow-up (HR = 1.210, p=0.364). In addition, VDD was not associated with an increased risk of pneumonia (HR = 1.053, p=0.823) or emergency visits at the 12-month follow-up (HR = 1.206, p=0.148). Conclusion: The results revealed no significant link between VDD and PSD risk during the 3-month and 12-month follow-up periods, suggesting that VDD might not play a substantial role in PSD risk. However, further extensive studies employing a prospective design are necessary to explore the potential protective effects of vitamin D against PSD and validate these findings.